Palliative Care: When finitude meets care (Research, Society and Development, 2024)
Palliative care management encompasses several important aspects that range from its indication and implementation to the reception of the patient and their families, especially when the death process at home is chosen. In this context, all care must be carried out comprehensively and individually, respecting the patient's own wishes as addressed in their advance directive. Primary Health Care together with the Home Care Service play a prominent role in this type of longitudinal care through the identification and early relief of possible physical, psychosocial and/or spiritual suffering. This article is a structured descriptive and reflective study in a bibliographic review of articles published between the years 2019 and 2023. The objective of this article is to carry out a study on palliative care in cases of personal and/or family choice for the process of death at home.